From physiological neck myoclonus to sleep related head jerk - Wolfensberger, Beat; Ferri, Raffaele; Bianco, Giovanni; Abbafati, Manuel; Miano, Silvia; Kaelin‐Lang, Alain; Bassetti, Claudio L.; Manconi, Mauro (Journal of sleep research, 2019)
Neck myoclonus (NM) is a frequent recently described sleep‐related motor phenomenon occurring mainly during REM sleep with uncertain effect on sleep continuity. To better describe this phenomenon we studied 11 consecutive drug‐free patients undergoing a video‐polysomnographic (V‐PSG) study who present at least 5 NM events in one single night of recording. All events were measured and checked for their association with rapid eye and leg movements, EEG arousals, awakenings and Bereitschaftspotential. One hundred and eighty‐two motor events from 11 subjects were analyzed. Motor events were approximately 0.5 s in duration and occurred during REM sleep in 79.7% of the cases. Only 14.8% of the events were associated with rapid eye movements, 52.2% with leg movements, while approximately 80% of them were accompanied by an arousal or awakening. No EEG abnormalities and Bereitschaftspotential were observed. For its duration and its segregation in sleep, NM could be more appropriately named “sleep‐related head jerks” (SRHJ). SRHJ should be recognized and its effect on sleep stability should be re‐considered.